CLOUD-DRIVEN OPTIMIZATION OF LECTURER PERFORMANCE DOCUMENT DIGITALIZATION USING AGILE UNIFIED PROCESS - Irawan, Rio; Inayah Syar, Nur (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2025)
The development of digital technology encourages universities to improve effectiveness and efficiency in data management, particularly in recording and reporting faculty performance. Some lecturers still face difficulties in reporting their performance in the SISTER application due to challenges in locating documents scattered across various archives, which often leads to issues such as delays in reporting, low information accuracy, and lack of transparency of faculty performance documents for institutional needs. This study aims to optimize the digitalization of faculty performance documents based on cloud computing using the Agile Unified Process (AUP) approach, which is implemented in the development of a cloud-based system by utilizing Google Drive as the storage medium for digital faculty performance documents. The AUP methodology was chosen for its ability to combine flexible iterative and incremental principles, allowing the system to adapt quickly and continuously to user needs. Testing using Equivalence Partitioning, based on the functional and non-functional requirements of the system, has shown results in accordance with expectations.